Plum Valley Hospital: A Critical Governance Matter Instructor's Note - Grunewald, Donald (Journal of business ethics, 2004)
This case involves the quandary of a businessman named Arthur Eldredge. A member of the Board of Trustees of Plum Valley Hospital, he is uneasy about apparent conflicts of interest among many board members. Further, Mr. Eldredge is unsure if he can fulfill his responsibilities to the Board. A trustee of the hospital, he thinks he should do something to resolve these issues. He is uncertain about what action to take.